Nilai-nilai Pendidikan Karakter dalam Kaba Urang Tanjung Karang pada Pertunjukan Dendang Pauh - Ananda, Refisa; Syafruddin, Syafruddin (Jurnal Sastra Indonesia, 2023)
This study aims to describe the values of character education contained in Kaba Urang Tanjuang Karang in the Dendang Pauah performance. The method used in this study is a descriptive-analytical method, this method aims to describe and analyze the pattern of character education in Kaba Urang Tanjuang Karang at the Dendang Pauah performance. Data collection is carried out by recording. The data of this study is the result of transcription of the Kaba Urang Tanjuang Karang manuscript. Based on the results of the study, it can be concluded that there are nine values of character education contained in Kaba Urang Tanjung Karang, namely religious, discipline, hard work, democratic, love of the homeland, respect for achievements, social care, peace-loving, and responsibility.